Unraveling the work–life policies puzzle: How the ‘ideal worker’ norm shapes perceptions of policies legitimacy and use - Tanquerel, Sabrina; Santistevan, Diana (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2022)
SummaryThe development of work–life policies—e.g., employee assistance programs, on-site childcare, flextime, part-time, compressed week, and so on—is increasingly important for a growing number of organizations. Though such programs provide benefits for both employees and employers, usage rates are still low. Scholars have called for research that addresses this phenomenon and more particularly explains the underlying processes of individual decision-making concerning work–life balance, and describe why and how certain social groups differ in their approaches to policy use. Our inductive study –based on 44 individual interviews- aims to address these issues. We found that the policies are used differently depending on the employees’ social group, and that certain salient social identities—such as gender, parenthood and managerial status—shape their use. Such programs are a structural and cultural change for organizations and often present an opportunity for redefining the centrality of work. Indeed the values inherent in them, including resting and taking time for oneself or for one’s family, may conflict with the traditionally masculine values associated with the ‘ideal worker’, intuitively linked to performance and production of positive results. The clash between the two, which permeated the interviews, causes employees to fall back on the social identity or identities they find meaningful. Our findings show three main strategies that individuals use when they feel that their social identity is threatened: (1) engage in workaround activities to avoid using work-life policies; (2) try to compensate for policies use (by engaging in projects outside one’s job or doing overtime work) ; and (3) significantly limit policies use. These results contribute to literature by showing that many managers and men do not feel legitimate to use work-life policies and find workarounds to manage without them, thus perpetuating stereotypical masculine norms. We demonstrate that the identity threat that underlies work-life policies taking may help women in the short term, but also contributes to their discrimination in the long run as well as is detrimental to the work-life balance of men.